2020
DOI: 10.1037/dev0000884
|View full text |Cite
|
Sign up to set email alerts
|

Robot teachers for children? Young children trust robots depending on their perceived accuracy and agency.

Abstract: Children acquire extensive knowledge from others. Today, children receive information from not only people but also technological devices, like social robots. Two studies assessed whether young children appropriately trust technological informants. One hundred and four 3-year-olds learned the names of novel objects from either a pair of social robots or inanimate machines, where 1 informant was previously shown to be accurate and the other inaccurate. Children trusted information from an accurate social robot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 21 publications
5
36
0
1
Order By: Relevance
“…found that VAs are most often not able to answer children's causal questions, yet they did not examine how children react in such instances. Furthermore, as mentioned earlier, children are selective in trusting digital tools, and they rely on accurate computers and robots over inaccurate ones from a young age(Brink & Wellman, 2020;Danovitch & Alzahabi, 2013). Our finding that older children veer off course upon receiving irrelevant and uninformative responses may have implications for their overall trust in VAs as a source of information.Our work contributes to the growing literature trying to better comprehend children's understanding of and interactions with VAs, highlighting the unique potential of VAs for children's learning, and raising several questions that need to be answered before concluding that these devices are effective for educational purposes.…”
supporting
confidence: 60%
See 1 more Smart Citation
“…found that VAs are most often not able to answer children's causal questions, yet they did not examine how children react in such instances. Furthermore, as mentioned earlier, children are selective in trusting digital tools, and they rely on accurate computers and robots over inaccurate ones from a young age(Brink & Wellman, 2020;Danovitch & Alzahabi, 2013). Our finding that older children veer off course upon receiving irrelevant and uninformative responses may have implications for their overall trust in VAs as a source of information.Our work contributes to the growing literature trying to better comprehend children's understanding of and interactions with VAs, highlighting the unique potential of VAs for children's learning, and raising several questions that need to be answered before concluding that these devices are effective for educational purposes.…”
supporting
confidence: 60%
“…Children are selective and critical in trusting digital sources such as the Internet and social robots (e.g., Brink & Wellman, 2020;Wang et al, 2019), and our finding that children seek factual information from VAs does not necessarily mean that they trust the information to apply to their daily lives. Furthermore, the prevalence of information-seeking questions in our data may have been influenced by the experimental setting: children may use VAs for a wider variety of purposes at home (Beneteau et al, 2020), as opposed to a zoo where listening to music or turning on the lights would make no sense.…”
Section: Discussionmentioning
confidence: 85%
“…Across several different domains, children are willing to interact with robots. For example, 3-year-old children will choose to learn information from social robots who give accurate (but not inaccurate) information and will also choose not to learn from inanimate toys that give either accurate or inaccurate names for items [27]. Further, 3-to-6-year-old children consider robots to be better sources for particular types of information, such as learning information about machines rather than about biology or psychology [28].…”
Section: Introductionmentioning
confidence: 99%
“…The other is that children perceive the robot as a tool or an object without an ability to have autonomy or its preferences, which is not helpful for researchers wanting to create a companion-like interaction with the robot. They are building trust towards a dependent agent which is not the same as believing in a robot's autonomy of agency [87]. There is a need for building further discussion around the role of teacher and how children would perceive the robot's agency without her in the room.…”
Section: (D)mentioning
confidence: 99%